Recent Status on Lactate Monitoring in Sweat Using Biosensors: Can This Approach Be an Alternative to Blood Detection? - Leonardo Messina; Maria Teresa Giardi (Biosensors)
Recent studies have shown that lactate is a molecule that plays an indispensable role in various physiological cellular processes, such as energy metabolism and signal transductions related to immune and inflammatory processes. For these reasons, interest in its detection using biosensors for non-invasive analyses of sweat during sports activity and in clinical reasons assessments has increased. In this minireview, an in-depth study was carried out on biosensors that exploited using electrochemical methods and innovative nanomaterials for lactate detection in sweat. This detection of lactate by biosensors in the sweat method seems to be feasible and highly desirable. From this commentary analysis, we can conclude that the correlation between lactate concentrations in sweat and blood is not yet clear, and studies are needed to clarify some key issues essential for the future application of this technology.